IMF Committee on Balance of Payments Statistics : Annual Report 1996. (Balance of Payments Statistics; Balance of Payments Statistics ;, 1997)
This annual report of the IMF Committee on Balance of Payments Statistics discusses the Committee's activities during 1996 and outlines its future work program.